A Theoretical Review on the Impact of EFL/ESL Students’ Self-Sabotaging Behaviors on Their Self-Esteem and Academic Engagement - Zhang, Fuhua (Frontiers in Psychology, 2022)
Learner emotions have been considerably emphasized in SLA research and practice with the advent of positive psychology. This has led to a surge of scholarly interest in this strand of research over the past years all around the world. However, the impact of students’ negative emotions such as self-sabotage that actually occur in english as a foreign language (EFL) classrooms on the construction and development of positive learner emotions like self-esteem and academic engagement has been mostly overlooked by second/foreign language researchers. Against this shortcoming, the present review article presented the theoretical and empirical underpinnings of these three crucial variables in SLA focusing on their conceptualizations, dimensions, typologies, related studies, and research gaps. Finally, the study offers a number of practical implications to [EFL/english as a second language (ESL)] teachers, students, teacher trainers, and SLA researchers in order to increase their awareness of learner emotions and the power of such feelings in language teaching and learning processes.